Pengaruh Metode Pelatihan Terhadap Ketepatan Servis Ditinjau Dari Koordinasi Mata Tangan Atlet Tenis Lapangan - Krisna Dewi, Ni Putu Wulan; Yoda, I. K.; Swadesi, I. K. I.; Dharmadi, M. A.; Danardani, W. (Departemen Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2024)
ABSTRACT Ni Putu Wulan Krisna Dewi, 2023. The Influence of Training Methods on Serving Accuracy as Seen from the Hand-eye Coordination of Field Tennis Athletes at the Tennis Club in Gianyar. Thesis (unpublished). Singaraja: UNDIKSHA Postgraduate Program This thesis has been corrected and checked by Supervisor I: Dr. I Ketut Yoda, M.Or, and Supervisor II: Dr. I Ketut Iwan Swadesi, S.Pd., M.Or. Competency in tennis skills is one of the aspects that must be mastered in playing tennis. However, sometimes this cannot be achieved due to inappropriate methods. This study aims to determine the effect of training methods on service accuracy in terms of hand-eye coordination of field tennis athletes at a tennis club in Gianyar. This type of research is a quasi-experimental research with a Posttest Only Non-Equivalent Control Group Design which involves a sample of 60 tennis athletes selected using the ordinal pairing technique. Data was collected using Hewitt's achievement test. Data analysis was carried out using descriptive statistics and a 2-way ANOVA test followed by the LSD test. The results of the study showed that the fixed target training method had a significantly better impact on tennis serve accuracy compared to the moving target method. There is an interaction between training methods and hand-eye coordination, where the fixed target training method is more suitable for athletes with high hand-eye coordination, but on the other hand, with low hand-eye coordination, the moving target method is more suitable. It was concluded that fixed target and moving target training methods can improve the accuracy of field tennis serves. Key words: training methods, service accuracy, hand eye coordination